Pemilihan Parameter Proses Pembubutan Dalam Menentukan Kekasaran Permukaan N7 Baja ST 41 - Lubis, Sobron; Kusuma , Heru Budi; Widjaya, Alvian Hartanto; Wibowo, Harry; Ken, Richard; Ariyanti, Silvi (Jurnal Teknik, 2025)
The turning process is a machining process on a cylindrical workpiece to produce a material profile as designed. The surface of the workpiece being machined produces rough scratches. The surface roughness of the workpiece is an indicator of the quality of the resulting surface. In machine construction, the surface roughness value has been determined by the designer according to the construction needs.The manufacturing process must be capable of forming metal and producing predetermined surface roughness values. The surface roughness value of the workpiece is influenced by several factors such as cutting parameters, cutting tools, coolant system, etc. This research was conducted to determine cutting parameters, especially cutting conductivity on the resulting surface roughness value. The study was carried out using a lathe and a carbide-type cutting tool to cut ST 41 steel. The cutting parameters were cutting speeds of 200, 215, 230, 245, and 260 (m/min), feeding, and depth of cut. Before machining is carried out, the cutting possibility of N7 is determined, namely 1.6 microns, based on the design of the shaft construction. To determine the roughness value to be achieved, the turning process is carried out by varying the cutting speed, cutting pass 0.1, 0.2, and 0.3 (mm/rev), while the depth of cut is 0.5 mm. After the cutting process is carried out, the surface roughness of the workpiece is measured. From the results of observations and measurements, it was found that the parameters closest to the desired surface roughness N7 (1.6) were cutting speed (Vc) 245 (m/min), feeding (f) 0.1 (mm/rev), and depth of cut (a) 0.1 mm with a roughness value of 1.63 µm.